2014
DOI: 10.1111/1467-8489.12051
|View full text |Cite
|
Sign up to set email alerts
|

A response to Doole and Marsh () article: methodological limitations in the evaluation of policies to reduce nitrate leaching from New Zealand agriculture

Abstract: A recent paper by Doole and Marsh (2013), questioned the validity of using the New Zealand Forest and Agriculture Regional Model (NZFARM) for New Zealand agri-environmental policy analysis. We respond to their critique by clearly describing the model structure, explaining the NZFARM parameterisation, calibration, and validation procedure, and presenting estimates from a series of nutrient reduction policy scenarios to highlight the utility of the model. In doing so, we demonstrate that NZFARM generates logical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Daigneault et al (2014) explain that NZFARM calibrates within 1-3% of the reported baseline without PMP, given the accuracy of the underlying farm level data. This would appear to support the case for not using PMP, as its omission would have little impact on model calibration, while also allowing the modellers to separate themselves from a wealth of research that has invalidated the application of this technique.…”
mentioning
confidence: 83%
“…Daigneault et al (2014) explain that NZFARM calibrates within 1-3% of the reported baseline without PMP, given the accuracy of the underlying farm level data. This would appear to support the case for not using PMP, as its omission would have little impact on model calibration, while also allowing the modellers to separate themselves from a wealth of research that has invalidated the application of this technique.…”
mentioning
confidence: 83%
“…Python 2.7 is used to facilitate a loose coupling [ 38 ] between ARLUNZ and a modified version of the New Zealand Forest and Agriculture Regional Model (NZFARM) that provides economic information within ARLUNZ. NZFARM is a comparative-static, non-linear, partial equilibrium mathematical programming model of New Zealand land use operating at the catchment scale [ 32 ]. The modified version used within ARLUNZ has been refined to produce an economically optimised result for each farm rather than an optimised landscape for an entire catchment.…”
Section: Methodsmentioning
confidence: 99%
“…The modified version used within ARLUNZ has been refined to produce an economically optimised result for each farm rather than an optimised landscape for an entire catchment. For more information about NZFARM, Daigneault et al [ 32 ] details its design, parameterisation and validation while Daigneault et al [ 39 – 42 ] discusses the input data used within model.…”
Section: Methodsmentioning
confidence: 99%
“…Python 2.7 is used to facilitate a loose coupling [64] between ARLUNZ and a modified version of the New Zealand Forest and Agriculture Regional Model (NZFARM) that provides economic information. NZFARM is a non-linear, partial equilibrium mathematical programming model of New Zealand land use operating at the sub-catchment scale [65]. The version used within ARLUNZ has been refined to produce an economically optimised result for each farm rather than an optimised landscape for a sub-catchment [66][67][68][69].…”
Section: Methodsmentioning
confidence: 99%